HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN KECEMASAN PADA PASIEN KANKER PAYUDARA - Zakiah Siti Nurjanah; Endang Fourianalistyawati (Universitas Bunda Mulia, 2013)
Based on data from the Cancer Hospital Dharmais (RSKD), from 2004 to 2010, breast cancer was always the top ranked. It showed that breast cancer is a serious disease in Indonesia. Psychological reactions that usually appear after a patient adjudged breast cancer is a mental shock, anxiety, could not accept the fact, to depression. Anxiety that occurs in patients with breast cancer will be reduced if the immediate environment, such as family, relatives, friends, and neighbors provide social support to the patient. This study aims to examine the relationship between social support with anxiety in breast cancer patients. This study involved 30 breast cancer patients with stage II and III age range 17-60 years. It was based on the assumption that patients in stage II and III may exhibit anxiety traits and still possible to join the study, and patients with an age range 17-60 years has had psychological maturity and be able to think logically. This research used quantitative methods using scale study, which was based on indicators which refer to the theory of social support by Sarafino (1998) and the theory of anxiety by Nevid (2005). The results of this study indicate that there was an association between social support with anxiety in breast cancer patients.Keywords: Breast cancer patients, social support, and anxiety